Breaking out of Unhealthy Marital Interactions - Eboni Baugh; Donna Davis (EDIS)
"For couples today, there's an abundance of information on how to sustain healthy, happy marital relationships. What many couples fail to realize is that these positive practices won't work without addressing negative patterns and destructive behaviors in their relationship." This 2-page radio transcript was written by Eboni Baugh and Donna Davis, and published by the UF Department of Family, Youth and Community Sciences, March 2012.